2015
DOI: 10.1080/1177083x.2015.1068185
|View full text |Cite
|
Sign up to set email alerts
|

Children with disabilities and disaster preparedness: a case study of Christchurch

Abstract: An estimated seven million children with disabilities worldwide are affected by disasters annually. This significant figure emphasises the particular vulnerability of these children in facing natural hazards. However, their needs as well as their capacity and role in disaster risk reduction have largely been overlooked by researchers and policymakers. This paper draws on a case study in Christchurch to identify insights, realities, possibilities and obstacles in relation to the involvement in disaster prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 29 publications
0
28
0
1
Order By: Relevance
“…While the need for inclusive strategies for all vulnerability dimensions is important in disaster plans, often factors related to mental health, anxiety, or stress were not considered (Grant 2018). Other researchers cited a lack of inclusion around mental health issues (Inter-Agency Standing Committee 2015; Stough and Kelman 2018), considerations for the deaf population (Pickering et al 2017;Bennett et al 2018;Craig et al 2019), and with regards to children with disasters (Ronoh et al 2015;Stough et al 2017).…”
Section: Understanding Disaster Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…While the need for inclusive strategies for all vulnerability dimensions is important in disaster plans, often factors related to mental health, anxiety, or stress were not considered (Grant 2018). Other researchers cited a lack of inclusion around mental health issues (Inter-Agency Standing Committee 2015; Stough and Kelman 2018), considerations for the deaf population (Pickering et al 2017;Bennett et al 2018;Craig et al 2019), and with regards to children with disasters (Ronoh et al 2015;Stough et al 2017).…”
Section: Understanding Disaster Riskmentioning
confidence: 99%
“…Building capacity among individuals at risk during disasters may aid in lessening their vulnerability, although many scholars found that not emphasizing human, social, and economic capital can thwart efforts. For example, children with general awareness and understanding of potential hazards in Christchurch, New Zealand may have an increased capacity to anticipate and cope with following the impact of an extreme event (Ronoh et al 2015). Similarly, allowing for independence among people with disabilities in shelters may increase their capacity; however, sheltering for people with disabilities is an under-researched area in Australia (Malpass et al 2019).…”
Section: Understanding Disaster Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Children do not constitute a homogeneous group: age, gender, ethnicity, and disability introduce diversity and require specific attention (Peek and Stough 2010;Ronoh et al 2015). Recent disasters revealed dramatic gaps, in first world countries, between ''affluent and low-income childhoods'' (Thorne 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…'Clergy views on their role in city resilience' (Brogt et al 2015) likewise points out the missed opportunities that come from approaching affected communities geographically, and as vulnerable and therefore helpless, rather than as already standing networks of support (as is found in faith-based communities) that feed across geographic, class and cultural differences. 'Children with disabilities and disaster preparedness: a case study of Christchurch' (Ronoh et al 2015) emphasises that while always already constituted as a special and particularly vulnerable group, children with disabilities and their care support networks have significant insight into and solutions to offer to bridge the gaps, contradictions and unintended exclusions generated in the spaces between generic disaster preparedness tools such as 'drop, cover and hold' and the realities of continuing care through emergency situations.…”
mentioning
confidence: 99%